A modified polypropylene-based film and its preparation method

By blending modified boron nitride nanosheets and modified benzoxazine with polypropylene resin, a stable multiphase structure is formed, which solves the problems of heat resistance, mechanical strength and flame retardancy of polypropylene films in lithium-ion battery current collectors, and realizes high-performance modified polypropylene base films.

CN120818198BActive Publication Date: 2025-11-14扬州博恒新能源材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511343431.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-11-14
Estimated Expiration
2045-09-19

AI Technical Summary

Technical Problem

Existing polypropylene films have problems such as insufficient heat resistance, poor mechanical strength and modulus, poor dimensional stability and poor flame retardancy in lithium-ion battery current collector applications. Furthermore, existing modification methods have limitations such as poor compatibility and reduced toughness.

Method used

Modified boron nitride nanosheets and modified benzoxazine were blended with polypropylene resin, and PP-g-MAH was used as an interfacial compatibilizer to form a stable multiphase structure. Combined with the synergistic effect of modified benzoxazine, the high temperature resistance, mechanical strength and flame retardancy of the material were improved.

Benefits of technology

It significantly improves the high temperature resistance, mechanical strength and flame retardancy of modified polypropylene base film, ensures material compatibility and mechanical properties, avoids interface defects, and is suitable for lithium-ion battery current collectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention relates to the field of current collector membranes, specifically to a modified polypropylene-based membrane and its preparation method. The modified polypropylene-based membrane, by weight, comprises: 100 parts polypropylene resin, 5-15 parts modified boron nitride nanosheets, 3-8 parts interface compatibilizer, 10-20 parts modified benzoxazine, 0.2-0.5 parts antioxidant, 0.1-0.3 parts ultraviolet absorber, and 0.2-0.5 parts slip agent. This invention prepares a modified polypropylene-based membrane using polypropylene resin as the main material. By introducing modified boron nitride nanosheets, modified benzoxazine, and other additives, a stable multiphase structure is formed. The components exhibit synergistic reinforcing effects, resulting in significant improvements in high-temperature resistance, mechanical strength, flame retardancy, and overall performance compared to ordinary polypropylene films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of current collector membranes, and more specifically to a modified polypropylene-based membrane and its preparation method. Background Technology

[0002] Lithium-ion batteries, as a new generation of green high-energy chemical power sources, have been widely used in consumer electronics, new energy vehicles, and energy storage power stations. The current collector is a key component of lithium-ion batteries, its main function being to collect current and support the electrode active materials. Currently, commercially available lithium-ion batteries typically use aluminum foil as the positive electrode current collector and copper foil as the negative electrode current collector. However, metal foils have drawbacks such as heavy weight, susceptibility to corrosion, and the potential for increased internal resistance due to volume changes during repeated charge-discharge cycles.

[0003] To improve battery energy density and safety, developing novel lightweight current collectors has become a key research direction in the industry. Polymer films, due to their light weight, good flexibility, and resistance to chemical corrosion, are considered potential alternatives to traditional metal current collectors. Among them, polypropylene (PP) has attracted attention due to its low cost, balanced mechanical properties, and good electrical insulation. However, ordinary polypropylene films have several inherent defects that severely limit their application in the current collector field: First, insufficient heat resistance. Polypropylene has a melting point of approximately 165℃ and a low heat distortion temperature (typically below 80℃). Under battery operation, especially under abuse conditions such as overcharging or short circuits, the local temperature may rise significantly, causing the polypropylene film to soften, melt, or even shrink, leading to internal short circuits and serious safety hazards. Second, the mechanical strength and modulus need improvement. Although polypropylene has a certain degree of toughness, its tensile strength and elastic modulus are still significantly lower than those of metal foil. As a current collector, the material needs sufficient mechanical strength to support the electrode slurry and withstand mechanical stresses such as rolling and shearing during battery assembly, preventing film tearing or deformation. Third, poor dimensional stability. Polypropylene is a semi-crystalline polymer with a large thermal shrinkage rate when heated, which can lead to unstable electrode structure and affect the long-term cycle life and consistency of the battery. Fourth, it has poor flame retardancy. Polypropylene is highly flammable, with a limiting oxygen index (LOI) of only about 18%, which can exacerbate the fire risk of the battery in the event of thermal runaway.

[0004] To improve the performance of polypropylene, existing technologies typically employ modification methods such as adding inorganic fillers (e.g., talc, calcium carbonate, silica) or blending with other polymers. However, these methods often have significant limitations: while adding large amounts of inorganic fillers can improve rigidity and heat resistance, it leads to a sharp decrease in film toughness, an increase in density, and increased brittleness; and blending with polar polymers often results in phase separation due to poor compatibility, forming macroscopic defects and ultimately deteriorating the overall performance.

[0005] In recent years, benzoxazine resins have been used for polymer modification due to their unique ring-opening polymerization behavior, high heat resistance, high char residue, and excellent flame retardant properties. However, directly blending traditional benzoxazine resins with polypropylene results in poor compatibility due to the significant differences in polarity and reactivity between the two, making it difficult to achieve uniform dispersion. Furthermore, benzoxazine resins are quite brittle after curing, which can lead to a significant reduction in the impact properties and elongation at break of the composite material.

[0006] Therefore, developing a high-performance polypropylene-based film suitable for lithium-ion battery current collectors, while maintaining the advantages of polypropylene such as its lightweight and easy processing, and fundamentally improving its high-temperature resistance, mechanical strength, toughness and flame retardancy, has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0007] In view of the problems existing in the prior art, the purpose of this invention is to provide a modified polypropylene-based film and its preparation method.

[0008] The objective of this invention is achieved through the following technical solution:

[0009] In a first aspect, the present invention prepares a modified polypropylene-based film, comprising, by weight parts:

[0010] 100 parts polypropylene resin, 5-15 parts modified boron nitride nanosheets, 3-8 parts polypropylene grafted maleic anhydride, 10-20 parts modified benzoxazine, 0.2-0.5 parts antioxidant, 0.1-0.3 parts ultraviolet absorber and 0.2-0.5 parts slip agent.

[0011] Preferably, the density of the polypropylene resin is 0.89-0.92 g / cm³. 3 The melt index is 6.0-10.0 g / 10 min (230℃ / 2.16 kg).

[0012] Preferably, the modified boron nitride nanosheets are boron nitride nanosheets modified with silane coupling agents.

[0013] More preferably, the method for preparing the modified boron nitride nanosheets includes:

[0014] Boron nitride nanosheets with a particle size of 100 nm were dispersed in an 80% ethanol solution, and coupling agent KH-550 was added. The mixture was refluxed for 4-6 hours, cooled to room temperature, filtered to collect the precipitate, washed 3-5 times with cold ethanol, and dried in a vacuum oven at 60°C for 1-2 hours to obtain modified boron nitride nanosheets.

[0015] The ratio of boron nitride nanosheets, KH-550 and ethanol solution was 0.5g:(0.08-0.16)g:(4-6)mL.

[0016] Preferably, the polypropylene is grafted with maleic anhydride (PP-g-MAH) with a grafting rate of 1.2%-1.5% and a melt index of 100-150 g / 10 min (190℃ / 2.16 kg).

[0017] Preferably, the antioxidant is a mixture of primary antioxidant 1010 and secondary antioxidant 168, and the mass ratio of primary antioxidant 1010 to secondary antioxidant 168 is 2-4:1.

[0018] Preferably, the ultraviolet absorber is at least one of UV-234, UV-360, and UV-531.

[0019] Preferably, the slip agent is erucamide or oleamide.

[0020] Preferably, the method for preparing the modified benzoxazine includes:

[0021] S1. Preparation of epoxy-functionalized benzoxazine (E-BOZ):

[0022] a. Weigh p-allylphenol and n-octylamine and mix them into a 1,4-dioxane ring. Use nitrogen as a protective gas and slowly add paraformaldehyde. Stir at 90-120℃ for 6-8 hours. After the reaction is complete, allyl-functionalized benzoxazine is obtained.

[0023] b. Weigh allyl-functionalized benzoxazine and add it to dichloromethane. Disperse it evenly in an ice-water bath. Slowly add m-chloroperoxybenzoic acid, maintain the ice-water bath and stir for 2-3 hours. Then gradually raise the temperature to room temperature and continue stirring for 8-12 hours. Wash and dry to obtain epoxy-functionalized benzoxazine (E-BOZ).

[0024] S2. Preparation of modified benzoxazine (Mod-BOZ);

[0025] Weigh out epoxy-functionalized benzoxazine (E-BOZ) and add it to N,N-dimethylformamide. After it is fully dissolved, add stearic acid-polyethylene glycol-amino and the catalyst tetrabutylammonium bromide (TBAB). Under nitrogen protection, heat to 80-85℃ and stir continuously for 10-12 hours. After the reaction is completed, precipitate, filter, wash, and vacuum dry to obtain modified benzoxazine (Mod-BOZ).

[0026] Preferably, in S1, the ratio of p-allylphenol, n-octylamine, paraformaldehyde and 1,4-dioxane is 1.34g:(1.21-1.37)g:(0.6-0.8)g:(40-60)mL.

[0027] Preferably, in S1, the ratio of allyl-functionalized benzoxazine, m-chloroperoxybenzoic acid and dichloromethane is 1.67 g:(0.96-1.15) g:(40-60) mL.

[0028] Preferably, in S2, the ratio of epoxy-functionalized benzoxazine, stearic acid-polyethylene glycol-amino and N,N-dimethylformamide is 1g:(0.6-0.8)g:(10-20)mL.

[0029] Preferably, in S2, the catalyst is tetrabutylammonium bromide (TBAB), and the amount added is 1%-3% of the mass of the epoxy-functionalized benzoxazine.

[0030] Secondly, the present invention provides a method for preparing a modified polypropylene-based film, comprising the following steps:

[0031] Step 1: Weigh all components according to the formula weight parts, put all raw materials into a high-speed mixer, stir and mix evenly to obtain mixed raw materials;

[0032] Step 2: The mixed raw materials are fed into a twin-screw extruder for melt blending, extruded and cast onto a cooling roller, and after cooling, a modified polypropylene film is obtained.

[0033] Step 3: The modified polypropylene film is pulled and wound up to obtain the modified polypropylene base film.

[0034] The beneficial effects of this invention are as follows:

[0035] 1. This invention prepares a modified polypropylene base film, using polypropylene resin as the main material. By introducing modified boron nitride nanosheets, modified benzoxazine, and other additives, a stable multiphase structure is formed. The components have a synergistic reinforcing effect, and the film has significant improvements in high temperature resistance, mechanical strength, and flame retardancy compared to ordinary polypropylene films.

[0036] 2. In the modified polypropylene base film of this invention, modified boron nitride nanosheets, as a two-dimensional nanomaterial, can effectively improve the mechanical strength, thermal conductivity, and thermal stability of the base film. Modified benzoxazine, used as a reinforcing agent, not only participates in curing and crosslinking to improve heat resistance and rigidity, but also produces a synergistic effect with boron nitride nanosheets, forming a denser material network structure. Furthermore, PP-g-MAH is used as an interfacial compatibilizer to ensure good compatibility between the components. The MAH groups can form strong chemical bonds or hydrogen bonds with the amino groups on the surface of the boron nitride nanosheets and the polar groups in the modified benzoxazine, greatly improving the interfacial compatibility between the polypropylene matrix components, ensuring effective stress transfer, and avoiding interfacial defects.

[0037] 3. The modified benzoxazine in this invention is obtained by modifying the traditional benzoxazine. The specific preparation process is as follows: first, allyl benzoxazine is epoxidized to introduce an active epoxy group into the benzoxazine; then, STA-PEG-NH2 with a long-chain alkyl group (stearic acid) and a flexible segment (PEG) is introduced through an epoxy-amino combination reaction, and finally the modified benzoxazine is prepared.

[0038] 4. Compared with traditional benzoxazine, the modified benzoxazine used in this invention not only significantly improves compatibility with the polypropylene matrix but also has a better performance-enhancing effect. Specifically, the introduced long-chain alkyl stearic acid groups enhance compatibility with the polypropylene matrix and also provide some lubrication, thereby reducing the need for additional lubricants. Meanwhile, the flexible PEG long chains, as the toughening segment of the system, effectively improve the brittleness of traditional benzoxazine resins after curing, enhancing both heat resistance and rigidity while also improving the toughness of the material. Detailed Implementation

[0039] To better understand the above technical solutions, exemplary embodiments of the present invention are described in more detail below. While exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to enable a more thorough understanding of the present invention and to fully convey the scope of the invention to those skilled in the art.

[0040] The present invention will be further described below with reference to the following embodiments.

[0041] Example 1

[0042] A modified polypropylene-based film, comprising, by weight parts:

[0043] 100 parts polypropylene resin, 10 parts modified boron nitride nanosheets, 6 parts polypropylene grafted maleic anhydride, 15 parts modified benzoxazine, 0.3 parts antioxidant, 0.2 parts ultraviolet absorber and 0.4 parts slip agent.

[0044] The density of the polypropylene resin is 0.91 g / cm³. 3 The melt flow index is 7.6 g / 10 min (230℃ / 2.16 kg). The polypropylene is grafted with maleic anhydride (PP-g-MAH) with a grafting rate of 1.3% and a melt flow index of 124 g / 10 min (190℃ / 2.16 kg). The antioxidant is a mixture of primary antioxidant 1010 and secondary antioxidant 168, with a mass ratio of 3:1. The ultraviolet absorber is UV-234. The slip agent is erucamide.

[0045] The method for preparing the modified boron nitride nanosheets includes:

[0046] 0.5 g of boron nitride nanosheets with a particle size of 100 nm were dispersed in 5 mL of 80 wt% ethanol solution, 0.12 g of coupling agent KH-550 was added, the mixture was refluxed for 5 h, cooled to room temperature, the precipitate was collected by filtration, washed 3 times with cold ethanol, and dried in a vacuum oven at 60 °C for 1 h to obtain modified boron nitride nanosheets.

[0047] The method for preparing the modified benzoxazine includes:

[0048] S1. Preparation of epoxy-functionalized benzoxazine (E-BOZ):

[0049] a. Add 1.34 g of allylphenol and 1.29 g of n-octylamine to 50 mL of 1,4-dioxane, stir thoroughly to dissolve, then purge with nitrogen as a protective gas, and slowly add 0.7 g of paraformaldehyde (molecular weight 30 g / mol). Stir and reflux at 110 °C for 7 h. After the reaction is complete, pour into 2 times the volume of n-hexane to precipitate, filter to collect the precipitate, wash with n-hexane 3 times, and dry in a vacuum oven at 60 °C for 18 h to obtain a white solid powder, which is allyl-functionalized benzoxazine.

[0050] b. Add 1.67g of allyl-functionalized benzoxazine to 50mL of dichloromethane, disperse it evenly in an ice-water bath, then slowly add 1.03g of m-chloroperoxybenzoic acid, controlling the temperature not to exceed 10℃. After all the acid has been added, stir in an ice-water bath for 2h, then gradually raise the temperature to room temperature and continue stirring for 10h. Wash the mixture three times with saturated sodium bicarbonate solution, then wash it three times with pure water. After removing the water, dry it under reduced pressure to remove the solvent, and obtain a pale yellow solid powder, which is epoxy-functionalized benzoxazine (E-BOZ).

[0051] S2. Preparation of modified benzoxazine (Mod-BOZ);

[0052] 1 g of epoxy-functionalized benzoxazine (E-BOZ) was weighed and added to 15 mL of N,N-dimethylformamide. After complete dissolution, 0.7 g of stearic acid-polyethylene glycol-amino (STA-PEG-NH2, PEG molecular weight 2000) and 2% by mass of tetrabutylammonium bromide (TBAB) catalyst were added. The mixture was heated to 85 °C under nitrogen protection and stirred continuously for 10 h. After the reaction was completed, the mixture was cooled and poured into 2 times the volume of ice-cold diethyl ether to precipitate. The precipitate was collected by filtration and washed 3 times with diethyl ether. The precipitate was dried in a vacuum oven at 60 °C for 18 h to obtain a pale yellow waxy solid, namely modified benzoxazine (Mod-BOZ).

[0053] The preparation method of the above-mentioned modified polypropylene-based film includes the following steps:

[0054] Step 1: Weigh all components according to the formula weight parts, put all raw materials into a high-speed mixer, and mix at 1000 rpm for 5 minutes at room temperature to obtain mixed raw materials;

[0055] Step 2: The mixed raw materials are fed into a twin-screw extruder for melt blending. The temperature range is 170-200℃, with zone 1 at 170℃, zone 2 at 180℃, zone 3 at 190℃, zone 4 at 195℃, the die head at 200℃, and the screw speed at 300 rpm. The extruded material is then cast to the cooling roller. After cooling, a modified polypropylene film is obtained.

[0056] Step 3: The modified polypropylene film is drawn and wound up at a production line speed of 60m / min, a draw ratio of 2.5:1, and a winding pressure of 5.8kN / m to obtain a modified polypropylene base film with a thickness of 15μm.

[0057] Example 2

[0058] A modified polypropylene-based film, comprising, by weight parts:

[0059] 100 parts polypropylene resin, 5 parts modified boron nitride nanosheets, 3 parts polypropylene grafted maleic anhydride, 10 parts modified benzoxazine, 0.2 parts antioxidant, 0.1 parts ultraviolet absorber and 0.2 parts slip agent.

[0060] The density of the polypropylene resin is 0.91 g / cm³. 3 The melt index is 7.6 g / 10 min (230℃ / 2.16 kg). The polypropylene grafted with maleic anhydride (PP-g-MAH) has a grafting rate of 1.3% and a melt index of 124 g / 10 min (190℃ / 2.16 kg). The antioxidant is a mixture of primary antioxidant 1010 and secondary antioxidant 168, with a mass ratio of 2:1. The ultraviolet absorber is UV-360. The slip agent is oleic acid amide. The preparation method of the modified benzoxazine is the same as in Example 1.

[0061] The method for preparing the modified boron nitride nanosheets includes:

[0062] 0.5 g of boron nitride nanosheets with a particle size of 100 nm were dispersed in 4 mL of 80 wt% ethanol solution, 0.08 g of coupling agent KH-550 was added, the mixture was refluxed for 5 h, cooled to room temperature, the precipitate was collected by filtration, washed 3 times with cold ethanol, and dried in a vacuum oven at 60 °C for 1 h to obtain modified boron nitride nanosheets.

[0063] The preparation method of the above-mentioned modified polypropylene-based film includes the following steps:

[0064] Step 1: Weigh all components according to the formula weight parts, put all raw materials into a high-speed mixer, and mix at 800 rpm for 10 minutes at room temperature to obtain mixed raw materials;

[0065] Step 2: The mixed raw materials are fed into a twin-screw extruder for melt blending. The temperature range is 170-200℃, with zone 1 at 170℃, zone 2 at 180℃, zone 3 at 190℃, zone 4 at 195℃, the die head at 200℃, and the screw speed at 200 rpm. The extruded material is then cast to the cooling roller. After cooling, a modified polypropylene film is obtained.

[0066] Step 3: The modified polypropylene film is drawn and wound up at a production line speed of 50m / min, a draw ratio of 3:1, and a winding pressure of 3.5kN / m to obtain a modified polypropylene base film with a thickness of 10μm.

[0067] Example 3

[0068] A modified polypropylene-based film, comprising, by weight parts:

[0069] 100 parts polypropylene resin, 15 parts modified boron nitride nanosheets, 8 parts polypropylene grafted maleic anhydride, 20 parts modified benzoxazine, 0.5 parts antioxidant, 0.3 parts ultraviolet absorber and 0.5 parts slip agent.

[0070] The density of the polypropylene resin is 0.91 g / cm³. 3 The melt index is 7.6 g / 10 min (230℃ / 2.16 kg). The polypropylene grafted with maleic anhydride (PP-g-MAH) has a grafting rate of 1.3% and a melt index of 124 g / 10 min (190℃ / 2.16 kg). The antioxidant is a mixture of primary antioxidant 1010 and secondary antioxidant 168, with a mass ratio of 4:1. The ultraviolet absorber is UV-531. The slip agent is erucamide. The preparation method of the modified benzoxazine is the same as in Example 1.

[0071] The method for preparing the modified boron nitride nanosheets includes:

[0072] 0.5 g of boron nitride nanosheets with a particle size of 100 nm were dispersed in 6 mL of 80 wt% ethanol solution, 0.16 g of coupling agent KH-550 was added, the mixture was refluxed for 5 h, cooled to room temperature, the precipitate was collected by filtration, washed 3 times with cold ethanol, and dried in a vacuum oven at 60 °C for 1 h to obtain modified boron nitride nanosheets.

[0073] The preparation method of the above-mentioned modified polypropylene-based film includes the following steps:

[0074] Step 1: Weigh all components according to the formula weight parts, put all raw materials into a high-speed mixer, and mix at 1200 rpm for 5 minutes at room temperature to obtain mixed raw materials;

[0075] Step 2: The mixed raw materials are fed into a twin-screw extruder for melt blending. The temperature range is 170-200℃, with zone 1 at 170℃, zone 2 at 180℃, zone 3 at 190℃, zone 4 at 195℃, the die head at 200℃, and the screw speed at 400 rpm. The extruded material is then cast to the cooling roller. After cooling, a modified polypropylene film is obtained.

[0076] Step 3: The modified polypropylene film is drawn and wound up at a production line speed of 80m / min, a draw ratio of 2:1, and a winding pressure of 7.0kN / m to obtain a modified polypropylene base film with a thickness of 20μm.

[0077] Example 4

[0078] A modified polypropylene-based film differs from Example 1 only in the preparation method of the modified benzoxazine.

[0079] The method for preparing the modified benzoxazine includes:

[0080] S1. Preparation of epoxy-functionalized benzoxazine (E-BOZ):

[0081] a. Add 1.34 g of allylphenol and 1.21 g of n-octylamine to 40 mL of 1,4-dioxane, stir thoroughly to dissolve, then purge with nitrogen as a protective gas, and slowly add 0.6 g of paraformaldehyde (molecular weight 30 g / mol). Stir the reaction at 90-120 °C for 6 h. After the reaction is complete, pour the mixture into 2 times the volume of n-hexane to precipitate the product. Filter to collect the precipitate, wash it 3 times with n-hexane, and dry it in a vacuum oven at 60 °C for 18 h to obtain a white solid powder, which is allyl-functionalized benzoxazine.

[0082] b. Add 1.67 g of allyl-functionalized benzoxazine to 40 mL of dichloromethane, disperse it evenly in an ice-water bath, and then slowly add 0.96 g of m-chloroperoxybenzoic acid, controlling the temperature not to exceed 10 °C. After all the acid has been added, stir in an ice-water bath for 2 h, then gradually raise the temperature to room temperature and continue stirring for 8 h. Wash the mixture three times with saturated sodium bicarbonate solution, then wash it three times with pure water. After removing the water, dry it under reduced pressure to remove the solvent, and obtain a pale yellow solid powder, which is epoxy-functionalized benzoxazine (E-BOZ).

[0083] S2. Preparation of modified benzoxazine (Mod-BOZ);

[0084] Weigh 1g of epoxy-functionalized benzoxazine (E-BOZ) and add it to 10mL of N,N-dimethylformamide. After it is fully dissolved, add 0.6g of stearic acid-polyethylene glycol-amino (STA-PEG-NH2, PEG molecular weight 1000) and 1% by mass of the epoxy-functionalized benzoxazine catalyst tetrabutylammonium bromide (TBAB). Under nitrogen protection, heat to 80℃ and stir continuously for 10h. After the reaction is completed, cool the mixture and pour it into 2 times the volume of ice-cold diethyl ether to precipitate. Filter to collect the precipitate and wash it 3 times with diethyl ether. Dry it in a vacuum oven at 60℃ for 12h to obtain a light yellow waxy solid, namely modified benzoxazine (Mod-BOZ).

[0085] Example 5

[0086] A modified polypropylene-based film differs from Example 1 only in the preparation method of the modified benzoxazine.

[0087] The method for preparing the modified benzoxazine includes:

[0088] S1. Preparation of epoxy-functionalized benzoxazine (E-BOZ):

[0089] a. Add 1.34 g of allylphenol and 1.37 g of n-octylamine to 60 mL of 1,4-dioxane, stir thoroughly to dissolve, then purge with nitrogen as a protective gas, and slowly add 0.8 g of paraformaldehyde (molecular weight 30 g / mol). Stir the reaction at 120 °C for 8 h. After the reaction is complete, pour the mixture into 2 times the volume of n-hexane to precipitate the product. Filter to collect the precipitate, wash it 3 times with n-hexane, and dry it in a vacuum oven at 60 °C for 18 h to obtain a white solid powder, which is allyl-functionalized benzoxazine.

[0090] b. Add 1.67g of allyl-functionalized benzoxazine to 60mL of dichloromethane, disperse it evenly in an ice-water bath, then slowly add 1.15g of m-chloroperoxybenzoic acid, controlling the temperature not to exceed 10℃. After all the acid has been added, stir in an ice-water bath for 3h, then gradually raise the temperature to room temperature and continue stirring for 12h. Wash the mixture three times with saturated sodium bicarbonate solution, then wash it three times with pure water. After removing the water, dry it under reduced pressure to remove the solvent, and obtain a pale yellow solid powder, which is epoxy-functionalized benzoxazine (E-BOZ).

[0091] S2. Preparation of modified benzoxazine (Mod-BOZ);

[0092] 1 g of epoxy-functionalized benzoxazine (E-BOZ) was weighed and added to 20 mL of N,N-dimethylformamide. After complete dissolution, 0.8 g of stearic acid-polyethylene glycol-amino (STA-PEG-NH2, PEG molecular weight 4000) and 3% by mass of tetrabutylammonium bromide (TBAB) catalyst were added. The mixture was heated to 85 °C under nitrogen protection and stirred continuously for 12 h. After the reaction was completed, the mixture was cooled and poured into 3 times the volume of ice-cold diethyl ether to precipitate. The precipitate was collected by filtration and washed 5 times with diethyl ether. The precipitate was dried in a vacuum oven at 60 °C for 24 h to obtain a pale yellow waxy solid, namely modified benzoxazine (Mod-BOZ).

[0093] Comparative Example 1

[0094] A modified polypropylene-based film, differing from Example 1 only in that the modified benzoxazine is replaced with conventional benzoxazine.

[0095] The method for preparing the benzoxazine includes:

[0096] Weigh 0.93 g of aniline and 0.94 g of phenol and add them to 30 mL of toluene. Then slowly add 0.7 g of paraformaldehyde (molecular weight 30 g / mol). Under nitrogen protection, heat to 110 °C and reflux with stirring for 7 h. After the reaction is complete, cool the reaction mixture to room temperature and pour it into 2 times the volume of n-hexane to precipitate. Filter to collect the precipitate and wash it 3 times with cold acetone. Dry it in a vacuum oven at 60 °C for 18 h to obtain a pale yellow solid powder, which is benzoxazine (BOZ).

[0097] Comparative Example 2

[0098] A modified polypropylene-based film, differing from Example 1 only in that the modified benzoxazine is replaced with epoxy-functionalized benzoxazine (E-BOZ), and the preparation process is the same as in Example 1.

[0099] Comparative Example 3

[0100] A modified polypropylene-based film differs from Example 1 only in that the modified benzoxazine is replaced with a mixture of benzoxazine (prepared in the same manner as Comparative Example 1), polyethylene glycol, and stearic acid. The mass ratio of benzoxazine, polyethylene glycol, and stearic acid is 1:0.62:0.08.

[0101] Experimental Example

[0102] The properties of the modified polypropylene films prepared in Examples 1 and Comparative Examples 1-3 were tested. The tests included mechanical properties, high-temperature resistance, and flame retardancy. Mechanical property tests included tensile strength (refer to GB / T 1040.3-2006), elongation at break (refer to GB / T 1040.3-2006), and modulus of elasticity (refer to GB / T 1040.3-2006). High-temperature resistance tests included heat distortion temperature (refer to GB / T 1634.2-2019) and heat shrinkage rate (120℃, 30min, refer to GB / T 13519-2016). Flame retardancy tests included limiting oxygen index (refer to GB / T 2406.2-2009).

[0103] The test results are shown in Table 1:

[0104] Table 1 Performance test results of polypropylene-based films with different modifications

[0105]

[0106] The test results above show that the modified polypropylene film prepared in Example 1 exhibits superior performance in terms of strength, toughness, high-temperature resistance, and flame retardancy, demonstrating the best overall performance and simultaneously possessing the advantages of high strength, high toughness, high-temperature resistance, and flame retardancy. Comparative Example 1 shows poor performance in strength, toughness, and high-temperature resistance, possibly because the traditional benzoxazine contains a large number of polar groups, resulting in poor compatibility with the non-polar polypropylene matrix. While Comparative Example 2 shows slightly higher elastic modulus and high-temperature resistance than Example 1, its tensile strength is lower, particularly its elongation at break, indicating poor toughness. This may be due to the epoxy groups of the epoxy-functionalized benzoxazine combining with PP-g-MAH in the composition, leading to increased molecular chain rigidity but significantly insufficient flexibility. In Comparative Example 3, stearic acid and PEG are merely physically mixed with the other components. While this enhances flexibility, it also sacrifices some strength, high-temperature resistance, and flame retardancy, resulting in performance inferior to Example 1 in all other aspects.

[0107] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A modified polypropylene-based film, characterized in that, Calculated by weight, including: 100 parts polypropylene resin, 5-15 parts modified boron nitride nanosheets, 3-8 parts polypropylene grafted maleic anhydride, 10-20 parts modified benzoxazine, 0.2-0.5 parts antioxidant, 0.1-0.3 parts ultraviolet absorber and 0.2-0.5 parts slip agent; The modified boron nitride nanosheets are boron nitride nanosheets modified with silane coupling agents. Among them, the modified benzoxazine is the product of the combined reaction of epoxy-functionalized benzoxazine and stearic acid-polyethylene glycol-amino; Methods for preparing epoxy-functionalized benzoxazine include: a. Weigh p-allylphenol and n-octylamine and mix them into a 1,4-dioxane ring. Use nitrogen as a protective gas and slowly add paraformaldehyde. Stir at 90-120℃ for 6-8 hours. After the reaction is complete, allyl-functionalized benzoxazine is obtained. b. Weigh allyl-functionalized benzoxazine and add it to dichloromethane. Disperse it evenly in an ice-water bath. Slowly add m-chloroperoxybenzoic acid, maintain the ice-water bath and stir for 2-3 hours. Then gradually raise the temperature to room temperature and continue stirring for 8-12 hours. Wash and dry to obtain epoxy-functionalized benzoxazine.

2. The modified polypropylene-based film according to claim 1, characterized in that, The density of the polypropylene resin is 0.89-0.92 g / cm³. 3 The melt index is 6.0-10.0 g / 10 min at 230℃ and 2.16 kg; the grafting rate of the polypropylene grafted with maleic anhydride is 1.2%-1.5%, and the melt index is 100-150 g / 10 min at 190℃ and 2.16 kg.

3. The modified polypropylene-based film according to claim 1, characterized in that, The method for preparing the modified boron nitride nanosheets includes: Boron nitride nanosheets with a particle size of 100 nm were dispersed in an 80% ethanol solution, and coupling agent KH-550 was added. The mixture was refluxed for 4-6 h, cooled to room temperature, filtered to collect the precipitate, and washed 3-5 times with cold ethanol. The precipitate was then dried in a vacuum oven at 60 °C for 1-2 h to obtain modified boron nitride nanosheets. The ratio of boron nitride nanosheets, KH-550 and ethanol solution was 0.5 g:(0.08-0.16) g:(4-6) mL.

4. The modified polypropylene-based film according to claim 1, characterized in that, The antioxidant is a mixture of primary antioxidant 1010 and secondary antioxidant 168, with a mass ratio of primary antioxidant 1010 to secondary antioxidant 168 of 2-4:

1.

5. The modified polypropylene-based film according to claim 1, characterized in that, The ultraviolet absorber is at least one of UV-234, UV-360, and UV-531; the slip agent is erucamide or oleamide.

6. The modified polypropylene-based film according to claim 1, characterized in that, The ratio of p-allylphenol, n-octylamine, paraformaldehyde, and 1,4-dioxane was 1.34 g:(1.21-1.37) g:(0.6-0.8) g:(40-60) mL.

7. The modified polypropylene-based film according to claim 1, characterized in that, The ratio of allyl-functionalized benzoxazine, m-chloroperoxybenzoic acid and dichloromethane was 1.67 g:(0.96-1.15) g:(40-60) mL.

8. The modified polypropylene-based film according to claim 1, characterized in that, The preparation method of the modified benzoxazine includes: Weigh out epoxy-functionalized benzoxazine and add it to N,N-dimethylformamide. After it is fully dissolved, add stearic acid-polyethylene glycol-amino and catalyst. Under nitrogen protection, heat to 80-85℃ and stir continuously for 10-12 hours. After the reaction is completed, precipitate, filter, wash, and vacuum dry to obtain modified benzoxazine.

9. A modified polypropylene-based film according to claim 8, characterized in that, The ratio of epoxy-functionalized benzoxazine, stearic acid-polyethylene glycol-amino and N,N-dimethylformamide is 1g:(0.6-0.8)g:(10-20)mL; the catalyst is tetrabutylammonium bromide, and the amount added is 1%-3% of the mass of epoxy-functionalized benzoxazine.

10. A method for preparing the modified polypropylene-based film according to claim 1, characterized in that, Includes the following steps: Step 1: Weigh all components according to the formula weight parts, put all raw materials into a high-speed mixer, stir and mix evenly to obtain mixed raw materials; Step 2: The mixed raw materials are fed into a twin-screw extruder for melt blending, extruded and cast onto a cooling roller, and after cooling, a modified polypropylene film is obtained. Step 3: The modified polypropylene film is pulled and wound up to obtain the modified polypropylene base film.

Citation Information

Patent Citations

  • Blended toughened modified polypropylene composite material and preparation method thereof

    CN110467773A

  • Fuel cell separator and method of manufacture

    US20030190516A1